Hubungan Islamic Self Esteem dengan Social Loafing pada Mahasiswa Program Studi Pendidikan Agama Islam - Fitri Maulan; Sutipyo Ru’iya (Jurnal Ilmiah Dikdaya, 2023)
This research started with students from the Ahmad Dahlan University Islamic Religious Education study program class of 2019 who did social loafing. The purpose of this study was to determine the level of self-esteem and social loafing in students of the Islamic Religious Education study program class of 2019 at Ahmad Dahlan University and also to find out whether there is a correlation between self- esteem and social loafing. This study uses a type of correlational quantitative research. The research population was students of the Ahmad Dahlan University Islamic Religious Education study program class of 2019 with a total of 383 students with a sample of 196 students. The number of samples obtained through the Slovin formula and sampling using probability sampling technique with simple random sampling. The independent variable in this study is self-esteem, while the dependent variable is social loafing. To measure the scale of the two variables, 24 statement items were used for each variable. Then the reliability value for the self-esteem scale is 0.855 and the social loafing scale is 0.910. In analyzing the correlation between the two variables, this study used the Pearson product moment correlation technique. The results showed that there was a negative and significant correlatin between self-esteem and social loafing in students of the Ahmad Dahlan University Islamic Religious Education Study Program class of 2019 with a correlation coefficient of -0.662 and a significance value of 0.000, namely <0.05. As for the description of the level of student self-esteem, it is included in the medium category with a percentage value of 69% and the level of social loafing is included in the medium category with a percentage value of 67%.